Relationship between Demographic Characteristics of Telehealth Users with the Satisfaction Level of @telmed.fkub Instagram Followers - Muhammad, Athaya Rahmanardi; Setijowati, Nanik; Dwi Rahayu, Indriati; Dasa Novita, Khuznita (Family Medicine Department, Faculty of Medicine, Brawijaya University, 2023)
Background: The @telmed.fkub account is a health promotion program of the Medical Faculty of Brawijaya University that provides health information services to the public. This program conducts regular evaluations to determine the effectiveness of services to the community. Objective: To evaluate this program in determining the user's satisfaction with appearance, usability, service, and willingness to recommend. Then, the level of satisfaction is linked to user demographic data, whether there is a relationship or not. Methods: This research uses a cross-sectional observational research method where data is collected by a Google Form questionnaire distributed randomly to Instagram account followers @telmed.fkub. The demographic variables were age, gender, education level, and educational background. The satisfaction level was categorized into five subtypes: appearance, service, usability, and willingness to recommend. These satisfaction levels were then measured on a five 5-level Likert scale. The Chi-Square or Fisher's Exact tests analyzed the collected data to determine the p-value. Results: The total number of respondents was 99. Most respondents are satisfied with the @telmed.fkub akun and program (96.97%). It was also shown that there was a significant relationship between the genders of @telmed.fkub users in telehealth display satisfaction, and there were no significant differences between age groups, education levels, and backgrounds education of @telmed.fkub users in telehealth satisfaction. Conclusion: There is a significant relationship between gender and appearance satisfaction levels of @telmed.fkub users.